(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Carpal Tunnel Syndrome (CTS) is a common upper extremity entrapment neuropathy that affects 4-5% of the general population, with a greater frequency in females. Electrodiagnostic investigations have been the standard method for diagnosing CTS, although they have limitations. A developing discipline for evaluating sensory nerve function is quantitative sensory testing (QST). The purpose of this study was to assess the effectiveness of QST-based transcutaneous electrical nerve stimulation (TENS) in patients with CTS. Methods: On 27 CTS patients, cross-sectional research was carried out. Evaluations of Neuropen, Semmes-Weinstein Monofilament Test (SWMT), pressure-pain threshold measures (algometer), and nerve conduction studies (NCS) were conducted in addition to clinical assessments. TENS was administered with a standard apparatus. Results: Of the NCS cases, 40% were classified as moderate, 28% as severe, and 32% as mild. Following TENS, the thumb algometer values rose in all categories, with notable variations between them. Significant improvements in algometer readings were also seen in the index finger after TENS. The anomalies in the SWMT readings decreased, going from 84.9% before TENS to 24.5% following TENS. The neuropen results did not vary between NCS categories. Conclusion: TENS treatment improved pressure-pain thresholds and decreased SWMT anomalies in CTS patients, as measured by QST, suggesting improved sensory function. These results support TENS's potential efficacy as a non-invasive, reasonably priced therapy for CTS sufferers, providing pain relief and improved sensory outcomes.